World Intellectual Property Report 2015 : Breakthrough Innovation and Economic Growth. - Organization, World Intellectual Property (World Intellectual Property Report., 2015)
WIPO's latest World Intellectual Property Report (WIPR) explores the role of IP at the nexus of innovation and economic growth, focusing on the impact of breakthrough innovations.